Interaction Gaps in PhD Education and ICT as a Way Forward: Results from a Study in Sweden - Aghaee, Naghmeh; Byron Jobe, William; Karunaratne, Thashmee; Smedberg, Åsa; Hansson, Henrik; Tedre, Matti (International Review of Research in Open and Distributed Learning, 2016)
Many research studies have highlighted the low completion rate and slow progress in PhD education. Universities strive to improve throughput and quality in their PhD education programs. In this study, the perceived problems of PhD education are investigated from PhD students’ points of view, and how an Information and Communication Technology Support System (ICTSS) may alleviate these problems. Data were collected through an online open questionnaire sent to the PhD students at the Department of (the institution’s name has been removed during the double-blind review) with a 59% response rate. The results revealed a number of problems in the PhD education and highlighted how online technology can support PhD education and facilitate interaction and communication, affect the PhD students’ satisfaction, and have positive impacts on PhD students’ stress. A system was prototyped, in order to facilitate different types of online interaction through accessing a set of online and structured resources and specific communication channels. Although the number of informants was not large, the result of the study provided some rudimentary ideas that refer to interaction problems and how an online ICTSS may facilitate PhD education by providing distance and collaborative learning, and PhD students’ self-managed communication.